Mechanical and Thermal Properties of Shale Ceramsite Concrete: Experimental Study on the Influence Law due to Microencapsulated Phase-Change Material Content and Phase-Change Cycle Numbers - Weihua Ding; Lin Zhu; Hu Li; Bin Hou; Fan Yang (Advances in Civil Engineering)
The addition of microencapsulated phase-change materials (MPCM) to concrete will inevitably cause changes in the mechanical and thermal properties of concrete, and this is vitally important for the safety and energy saving of concrete building components. In this research, shale ceramsite and shale ceramics sand were used as the main raw materials to produce lightweight aggregate concrete (LWAC) mixed with MPCM. In order to investigate the effect of MPCM content and phase-change cycle numbers on the mechanical and thermal properties of MPCM-LWAC, two groups of MPCM-LWAC specimens were prepared. One group consists of specimens containing 2.5%, 5.0%, 7.5%, and 10% MPCM, respectively, and they are used to reveal the change law of tensile strength, compressive strength, enthalpy, and specific heat capacity of LWAC integrated into MPCM. The other group includes specimens with the same MPCM content, but the specimens are subjected to different phase-change cycle numbers of 50, 100, 150, and 200 at the environment temperature of −10–60°C to study the thermal properties of MPCM-LWAC. Findings from the experimental results include the following: (1)The tensile and compressive strengths of MPCM-LWAC concrete are negatively correlated with the MPCM content, while the enthalpy and specific heat capacity are positively correlated with the MPCM content. When the MPCM content reaches 10%, the compressive and tensile strengths of MPCM-LWAC decreased, respectively, by 45.49% and 52.63% than the LWAC without MPCM. (2) Under heating and curing condition, the corresponding maximum specific heat capacity of LWAC with 10% MPCM is 328.35% and 249.50% higher than the LWAC without MPCM, respectively, and the average specific heat capacities increase 71.21% and 44.94%, respectively. (3) The melting enthalpy of MPCM-LWAC is slightly larger than the curing enthalpy, and the difference is more noticeable with the increase of MPCM content. In addition, when the number of phase-change cycle is below 200, the compressive strength and splitting tensile strength of MPCM-LWAC decrease by less than 5%, and the specific heat capacity decreases by less than 1.33%. Hence, it concludes that shale ceramsite concrete with MPCM has promising application prospects.